Two medicolegal autopsy cases of multinodular and vacuolating neuronal tumor revealed by postmortem MRI - Makino, Yohsuke; Kojima, Masatoshi; Inokuchi, Go; Motomura, Ayumi; Arai, Nobutaka; Inoue, Hiroyuki; Kabasawa, Hiroyuki; Iwase, Hirotaro; Yajima, Daisuke (Legal Medicine, 2024)
•Two medicolegal cases with the MVNT are shown.•The MVNT is epileptogenic and can cause sudden death.•MVNTs are difficult to detect by conventional autopsy.•Pre- or post-autopsy MRI is useful not to miss the MVNT. The multinodular and vacuolating neuronal tumor (MVNT) is a recently recognized brain lesion. MVNT has a characteristic appearance in MRI images and is potentially epileptogenic. To the best of our knowledge, no report has yet described this pathological entity in the forensic medicine literature. We present two medicolegal autopsy cases where postmortem MRI (PMMR) was useful to detect this lesion. Case 1: a man in his 30s, with about a 7-year history of intractable epilepsy and known MVNT died suddenly. Although MVNT was not detected in the initial morphological evaluation during autopsy, PMMR of the formalin-fixed brain revealed the lesion in the left frontal lobe. Histopathology confirmed it as a MVNT. Case 2: a man in his 20s hanged himself to death. PMMR prior to autopsy revealed MVNT in his brain, and the diagnosis was confirmed by a detailed histopathological evaluation. In both cases, postmortem CT was not useful for evaluation. The cases suggested that MVNT can cause sudden, unexpected epileptic death, and pre- or post-autopsy PMMR may be useful to detect it.